2000
DOI: 10.1128/mcb.20.2.453-461.2000
|View full text |Cite
|
Sign up to set email alerts
|

p21-Activated Kinase 1 Phosphorylates the Death Agonist Bad and Protects Cells from Apoptosis

Abstract: Bad is a critical regulatory component of the intrinsic cell death machinery that exerts its death-promoting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
267
5
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(281 citation statements)
references
References 63 publications
8
267
5
1
Order By: Relevance
“…The inhibitory effect of LY294002 on the level of Bad Ser112 phosphorylation is noteworthy, because it indicates that Akt-mediated phosphorylation of Ser136 precedes the phosphorylation of Ser112, the latter of which is assumed to be caused by RSK1, PAK1 or PKA [30][31][32]. PAK1 has been found to phosphorylate Bad at Ser136 and 112 and to protect fibroblasts and FL5.12 lymphoid progenitor cells from apoptosis [32].…”
Section: Doxorubicin-induced P38 Mapk Activation Negatively Regulatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibitory effect of LY294002 on the level of Bad Ser112 phosphorylation is noteworthy, because it indicates that Akt-mediated phosphorylation of Ser136 precedes the phosphorylation of Ser112, the latter of which is assumed to be caused by RSK1, PAK1 or PKA [30][31][32]. PAK1 has been found to phosphorylate Bad at Ser136 and 112 and to protect fibroblasts and FL5.12 lymphoid progenitor cells from apoptosis [32].…”
Section: Doxorubicin-induced P38 Mapk Activation Negatively Regulatesmentioning
confidence: 99%
“…PAK1 has been found to phosphorylate Bad at Ser136 and 112 and to protect fibroblasts and FL5.12 lymphoid progenitor cells from apoptosis [32]. PAK1 can be activated by the small GTPases Rac and Cdc42, and either of those GTPases can be activated by inhibition of PI3-K, which may explain the weak effect of LY294002 treatment on phosphorylation of Bad.…”
Section: Doxorubicin-induced P38 Mapk Activation Negatively Regulatesmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The cytotoxic effects of BAD are controlled by mechanisms that regulate its phosphorylation on at least two distinct serine residues, S112 and S136. [16][17][18] Previously, we showed that phosphorylation at either site is sufficient to protect prostate cancer cells from apoptosis. [19][20][21] We also showed that BAD promotes prostate tumor growth in mouse models.…”
mentioning
confidence: 99%
“…When Bad is serine phosphorylated on these functional residues, its proapoptotic function is suppressed by increasing its association with 14-3-3z and by decreasing its association with bcl-xL or bcl-2 at the mitochondrial membrane. 14,[24][25][26] Thus, B2 overexpression increases the threshold for mitochondrial release of sequestered apoptogenic proteins (cytochrome c and AIF) and markedly reduces apoptosis during serum starvation or staurosporine treatment.…”
Section: Discussionmentioning
confidence: 98%